Determination of the optimal packing configuration of a catalytic fixed-bed reactor using geometry and multi-objective optimization methods - Courtais, Alexis; Lesage, Francois; Privat, Yannick; Latifi, Abderrazak M. (2021 23rd International Conference on Process Control (PC), 2021)
This paper deals with the development of a geometry optimization approach to determine the optimal shape of a fixed-bed reactor where a catalytic surface reaction takes place. The investigated problem is formulated as a multi-objective optimization problem considering two antagonistic objectives: the energy dissipation in the fluid and the average concentration of reactant at the reactor outlet. The optimal solutions are subject to four constraints: (i) the process model consisting of the NavierStokes, the continuity and the convection-diffusion equations, (ii) an iso-volume constraint and (iii) two thickness constraints which allow us to take into account the manufacturability of the optimal reactors. The solution of the optimization problem is computed using the adjoint system method and the linear scalarization method which tranforms the multi-objective problem into a single-objective problem. The solution of the problem is a whole set of solutions (i.e. Pareto front) and the best optimal solution is chosen using the multi-attribute utility theory (MAUT). The best optimal shape of the reactor leads to a significant improvement of the conversion rate of 12.6% with respect to the initial shape and to an increase in energy dissipation 3.5 times higher.